2016
DOI: 10.2527/jas.2016-0737
|View full text |Cite
|
Sign up to set email alerts
|

Principal component analysis of breeding values for growth and reproductive traits and genetic association with adult size in beef cattle1

Abstract: Principal component analysis was applied to evaluate the variability and relationships among univariate breeding values predicted for 9 weaning and yearling traits, as well as suggest functions of the traits that would promote a particular breeding objective. Phenotypic and pedigree information from 600,132 Nelore animals was used. Genetic parameters and breeding values were obtained from univariate analyses of birth to weaning weight gain; weaning to yearling weight gain; conformation, finishing precocity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 19 publications
1
24
0
1
Order By: Relevance
“…This is in part due to differentially expressed genes associated either with muscle mass or fat deposition in the carcass (Bernard et al, 2009). Specialised beef breeds are generally late-maturing and fatten later than unimproved and dairy breeds (Albert ı et al, 2005;Boligon et al, 2016). However, the variation in meat colour observed the present study is not related to fatness as assessed by intramuscular fat deposition (Christensen et al, 2011) Red, Jersey and Holstein as unimproved and dairy breeds.…”
Section: Colour Variables: Principal Component Analysis Means and CLmentioning
confidence: 54%
See 1 more Smart Citation
“…This is in part due to differentially expressed genes associated either with muscle mass or fat deposition in the carcass (Bernard et al, 2009). Specialised beef breeds are generally late-maturing and fatten later than unimproved and dairy breeds (Albert ı et al, 2005;Boligon et al, 2016). However, the variation in meat colour observed the present study is not related to fatness as assessed by intramuscular fat deposition (Christensen et al, 2011) Red, Jersey and Holstein as unimproved and dairy breeds.…”
Section: Colour Variables: Principal Component Analysis Means and CLmentioning
confidence: 54%
“…Specialised beef breeds are generally late‐maturing and fatten later than unimproved and dairy breeds (Albertí et al ., ; Boligon et al ., ). However, the variation in meat colour observed the present study is not related to fatness as assessed by intramuscular fat deposition (Christensen et al ., ) or the dissected rib fat content (Albertí et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…(2013) and Boligon et al. (2016) suggested that principal components can be used as a selection index. The indices commonly used in horses for morphometric traits have empirical weight and do not consider the genetics correlations between variables (breeding values) (Cabral, 2004; Lucena et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…According to Boligon et al. (2016), this approach addresses the correlations between variables and may be considered a new composite trait. According to Vargas et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation